Improving Student Learning Outcomes Through the Project Based Learning Model with Elementary School Student Diorama Media - Rizky, Kavita Hataru Cipta; Hemalia, Hemalia; Koestanti, Jeny; Tahriza, Fitra Nabila (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: The purpose of this study was to improve the learning outcomes of fourth grade students at SD 5 Karangbener on the material of ethnic diversity and local wisdom through the application of the Project Based Learning (PjBL) model with diorama media. Research Methods: This research used a Classroom Action Research (PTK) approach carried out in two cycles, with steps of planning, implementation, observation, and reflection. Finding/Results: The results showed that before the application of PjBL, only 26.32% of students reached the Criteria for Achievement of Learning Objectives (KKTP). After the application of PjBL in the first cycle, the percentage of completeness increased to 57.89%, and in the second cycle it reached 89.5%. In addition to the quantitative improvement in learning outcomes, observations also recorded student participation and enthusiasm in the learning process. Thus, it can be concluded that the application of the PjBL model supported by diorama media has a positive effect in improving students' understanding of the material and fostering a positive attitude towards cultural diversity. Conclusion: This research recommends the use of PjBL as an effective learning method at the elementary level.